Toner and its manufacturing method

JP7631099B2Active Publication Date: 2025-02-18CANON KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021089684
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-28
Publication Date
2025-02-18
Estimated Expiration
2041-05-28

AI Technical Summary

Benefits of technology

【0006】 本発明によれば、ベタ追従性良化と、過帯電抑制による画像の濃度ムラ抑制を達成でき、かつ長期の耐久を通してトナーの劣化が少ないトナーを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631099000001
    Figure 0007631099000001
  • Figure 0007631099000002
    Figure 0007631099000002
  • Figure 0007631099000003
    Figure 0007631099000003
Patent Text Reader

Abstract

To provide a toner which can achieve good solid followability and suppression of image density unevenness due to suppression of excess charging, and is reduced in degradation of a toner through long-term durability.SOLUTION: A toner has toner particles containing a binder resin, wherein polyacid metal salt particles of a compound containing at least one metal element selected from metal elements included in groups 3 to 13 and a polyacid exist on the surface of the toner particles, when in a reflection electron image of the toner photographed by a scanning electron microscope at magnification of 50,000, with respect to the total number of the polyacid metal salt particles, a number ratio (%) of the area of the polyacid metal salt particles of 100 nm2 or less is represented by A, and a number ratio of the area of the polyacid metal salt particles of 500 nm2 or more is represented by B, they satisfy the following expression (1): 83.0≤A and expression (2): 1.7≤B≤17.0, and in the reflection election image, a ratio of the area of the polyacid metal salt particles having the area of 100 nm2 or less is 0.3% or more and 16.0% or less with respect to the total area of the surface of the toner particles in an observed visual field.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner used in a recording method utilizing an electrophotographic method, an electrostatic recording method, and a toner jet recording method. [Background technology]

[0002] In recent years, the fields in which electrophotographic image formation is used have become more diverse, ranging from printers and copiers to commercial printing machines. Accordingly, the demand for higher image quality, higher speed, and higher durability for electrophotography has been increasing. In addition, as the uses have become more diverse, the demand for smaller and lighter bodies has also been increasing. In order to achieve high image quality, toner is required to reproduce a latent image faithfully. In order to reproduce a latent image faithfully, it is effective to precisely control the charge of the toner. If the charge control of the toner is insufficient, problems such as fog caused by low charge toner developing in non-image areas, and uneven density of the image caused by regulation failure due to overcharged toner strongly adhering to the toner carrier occur, which are factors that hinder the faithful reproduction of the latent image. For this reason, in order to improve image quality, there have been many studies into controlling the charge of the toner by attaching a material whose chargeability can be precisely controlled to the toner surface or by coating the toner surface with a material that has excellent chargeability. Patent Document 1 discloses a toner that achieves suppression of overcharging by externally adding fine alumina particles that have been surface-treated with an organosilicon compound to the toner. Patent Document 2 discloses a toner having a layer containing an organosilicon polymer containing a polyvalent acid metal salt on the surface of a toner particle, and by controlling the average area of ​​the polyvalent acid metal salt and the coefficient of variation of the area of ​​the polyvalent acid metal salt, the toner has improved charge rise properties, is capable of suppressing overcharging of the toner, and also suppresses contamination of components. On the other hand, in order to increase the speed, it is necessary to supply toner quickly to developing members such as developing rollers, so density stability from the second sheet onwards (hereinafter referred to as solid image tracking) becomes an issue, especially when continuously printing images with a very high print rate (hereinafter referred to as solid image). In order to stabilize the density of solid images, it is necessary to continue to supply the necessary amount of toner to developing members such as developing rollers even during high-speed printing. Patent Document 3 discloses a toner that suppresses the aggregation of toner on a developing roller by controlling the force between two toner particles, thereby improving solid printing performance, and further discloses a toner that has an organosilicon polymer on its surface to make the surface charge distribution within the toner particles uniform, thereby improving transfer dust (the phenomenon in which toner scatters around characters or line images) and half-tone reproducibility. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 8-184988 [Patent Document 2] JP 2019-128516 A [Patent Document 3] JP 2020-71363 A Summary of the Invention [Problem to be solved by the invention]

[0004] The toner described in Patent Document 1 is excellent at suppressing uneven density in images, but the adhesion to the base material is insufficient when the alumina powder is simply mechanically added to the outside. When the toner is subjected to a large shear as the printing process becomes faster, the additive comes off during durability, and further, the detached additive contaminates parts, causing problems such as development streaks. The toner described in the above Patent Document 2 suppresses overcharging, and also suppresses contamination of components by the presence of the polyvalent metal salt together with a layer containing an organosilicon condensate. However, although Patent Document 2 describes that the form of the polyvalent metal salt is preferably fine particles, it does not pay attention to the significance and function of small-diameter polyvalent metal salt particles and large-diameter polyvalent metal salt particles, and does not control the number ratio of the two. Therefore, in response to the recent demand for high speed and miniaturization without a toner supplying member, the amount of toner supplied to the developing member is insufficient, and the problem of reduced solid followability remains. The toner described in Patent Document 3 above has a uniform surface charge distribution within the toner particles, but the uniform surface charge distribution within a single toner particle alone cannot eliminate the charge bias between toner particles. Therefore, the suppression of density unevenness by suppressing overcharging is insufficient, and further improvement is required to achieve the image quality level required in the future. In addition, in response to the recent demand for high speed and miniaturization without a toner supply member, the amount of toner supplied to the developing member is insufficient, and the problem of reduced solid followability remains. The present invention provides a toner that can solve the above problems, can eliminate uneven density in images by suppressing overcharging, has good solid image conformability, and causes little member contamination even over long-term use. [Means for solving the problem]

[0005] The present invention provides a toner having toner particles containing a binder resin, polyvalent acid metal salt particles of a polyvalent acid and a compound containing at least one metal element selected from the metal elements included in Groups 3 to 13 are present on the surface of the toner particles, In a backscattered electron image of the toner taken at a magnification of 50,000 times using a scanning electron microscope, the area of ​​the polyvalent acid metal salt particles relative to the total number of the polyvalent acid metal salt particles is 100 nm 2 The following number ratio (%) is A, the area of ​​the polyvalent acid metal salt particles is 500 nm 2 When the percentage (%) of the number of particles is B, the following formula (1) and formula (2) are satisfied, 83.0≦A (1) 1.7≦B≦17.0 (2) In the reflected electron image, the area of ​​100 nm 2 The toner is characterized in that the area ratio of the polyvalent acid metal salt particles is 0.3% or more and 16.0% or less. The present invention also provides a method for producing the toner having the above-mentioned configuration, The present invention relates to a method for producing a toner, characterized in that polyvalent acid metal salt particles made of a compound containing at least one metal element selected from the metal elements included in Groups 3 to 13 and a polyvalent acid are produced by reacting the compound containing the metal element with a polyvalent acid in an aqueous medium containing toner base particles and an organosilicon compound. Effect of the Invention

[0006] According to the present invention, it is possible to provide a toner which can improve the solid image conformability and suppress uneven density of an image by suppressing overcharging, and which is less susceptible to deterioration over a long period of use. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] In the present invention, the expressions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the lower and upper limit endpoints, unless otherwise specified.

[0008] In the toner charging process, friction between the charging member or carrier (hereinafter collectively referred to as the charging member) and the toner does not occur uniformly, which may result in overcharged toner and low-charged toner. In order to suppress overcharging of the toner, it is effective to increase the conductive path between the overcharged toner and low-charged toner and to make the charge distribution of the toner particles uniform. In addition, in order to quickly transfer the charge inside the toner to the outside, it is necessary to improve the conductivity between the toner base and the shell layer (the surface layer of the toner particle).

[0009] Furthermore, in order to improve solid print conformability, it is no longer sufficient to meet the recent demands for higher speeds simply by controlling the fluidity and cohesiveness of the toner, as has been done in the past; it is necessary to further increase the supply of toner to developing members such as developing rollers by utilizing a force that can more actively transport toner to the developing member.

[0010] Furthermore, if one tries to achieve overcharging control and improved solid-printing performance using external additives, the additives will come off over long periods of use, causing contamination of components and developing streaks and other problems, so a means other than external addition is necessary.

[0011] As a result of extensive research, the present inventors have found that in order to suppress uneven density in an image due to excessive charging and to improve solid image conformity, a toner having the following composition satisfies the above requirements.

[0012] That is, a toner containing toner particles having a binder resin, wherein polyvalent acid metal salt particles of a polyvalent acid and a compound containing at least one metal element selected from the metal elements included in Groups 3 to 13 are present on the surface of the toner particles, In a backscattered electron image of the toner taken at a magnification of 50,000 times using a scanning electron microscope, the area of ​​the polyvalent acid metal salt particles relative to the total number of the polyvalent acid metal salt particles is 100 nm 2 The following number ratio (%) is A, the area of ​​the polyvalent acid metal salt particles is 500 nm 2 When the percentage (%) of the number of particles is B, the following formula (1) and formula (2) are satisfied, 83.0≦A (1) 1.7≦B≦17.0 (2)

[0013] In the reflected electron image, the area of ​​100 nm 2 The above requirement is met when the area ratio of the polyvalent acid metal salt particles is 0.3% or more and 16.0% or less.

[0014] The present inventors consider the mechanism of the effect to be as follows.

[0015] In order to control the charge, it is necessary to quickly transfer the charge inside the toner to the shell layer and the low-charge toner present in the vicinity of the overcharged toner. On the surface of the toner particles of the present invention, there is a polyvalent acid metal salt of a polyvalent acid and a compound containing at least one metal element selected from the metal elements included in Groups 3 to 13. The metal elements included in Groups 3 to 13 have a valence of 2 or more, and the divalent or more acid forms a crosslinked structure with the metal element, and the crosslinked structure promotes the transfer of charge and suppresses overcharging.

[0016] In particular, salts composed of a metal element included in Groups 3 to 13 and a polyvalent acid have lower water absorption properties than salts containing only metal elements from Groups 1 and 2, and therefore show less change in performance in terms of the effect of suppressing overcharging over long-term use and the improvement of solid print conformability, which will be described later.

[0017] It is more preferable that the metal element is a Group 4 element. Group 4 elements are most stable when their oxidation number is +4. Therefore, they form a crosslinked structure with the polyvalent acid, and this crosslinked structure promotes the transfer of charges and suppresses overcharging.

[0018] Specific examples of metal elements used in the present invention include titanium (Group 4, electronegativity: 1.54), zirconium (Group 4, electronegativity: 1.33), aluminum (Group 13, electronegativity: 1.61), zinc (Group 12, electronegativity: 1.65), indium (Group 13, electronegativity: 1.78), hafnium (Group 4, electronegativity: 1.30), iron (Group 8, electronegativity: 1.83), copper (Group 11, electronegativity: 1.90), and silver (Group 11, electronegativity: 1.93).

[0019] The polyvalent acid used in the present invention may be any acid having a valence of two or more.

[0020] A salt formed from a divalent or higher acid and the above-mentioned metal element creates a crosslinked structure between the compound containing the metal element and the polyvalent acid, and this crosslinked structure promotes the transfer of electrons, thereby making it possible to suppress overcharging.

[0021] Specific examples of polyvalent acids used in the present invention include inorganic acids such as phosphoric acid (trivalent), carbonic acid (divalent), and sulfuric acid (divalent); and organic acids such as dicarboxylic acid (divalent) and tricarboxylic acid (trivalent). Specific examples of organic acids include dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, maleic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, and terephthalic acid; and tricarboxylic acids such as citric acid, aconitic acid, and trimellitic anhydride. Among these, phosphoric acid, carbonic acid, and sulfuric acid are preferred, and phosphoric acid is more preferred.

[0022] Specific examples of polyvalent acid metal salts combining the above metals and the above polyvalent acids include metal phosphates such as titanium phosphate compounds, zirconium phosphate compounds, aluminum phosphate compounds, copper phosphate compounds, and other metal sulfates such as titanium sulfate compounds, zirconium sulfate compounds, aluminum sulfate compounds, and other metal carbonates such as titanium carbonate compounds, zirconium carbonate compounds, aluminum carbonate compounds, and other metal oxalates such as titanium oxalate compounds, etc. Among these, metal phosphates are preferred because the phosphate ions crosslink the metals, resulting in high strength, and titanium phosphate compounds are more preferred.

[0023] The method for obtaining the polyvalent acid metal salt is not particularly limited, and any conventionally known method can be used. Among them, a method for obtaining the polyvalent acid metal salt by reacting a metal compound serving as a metal source with a polyvalent acid ion in an aqueous medium is preferred.

[0024] When a polyvalent acid metal salt is obtained by the above-mentioned method, any conventionally known metal compound can be used as the metal source without particular limitation, so long as it is a metal compound that gives a polyvalent acid metal salt by reaction with a polyvalent acid ion.

[0025] Among these, metal chelates are preferred because the reaction is easy to control and they react quantitatively with polyvalent acid ions, and lactate chelates such as titanium lactate and zirconium lactate are more preferred from the viewpoint of solubility in aqueous media.

[0026] Specific examples of the metal source used in the present invention include metal chelates such as titanium lactate, titanium tetraacetylacetonate, titanium lactate ammonium salt, titanium triethanolamine, zirconium lactate, zirconium lactate ammonium salt, aluminum lactate, aluminum trisacetylacetonate, and copper lactate; and metal alkoxides such as titanium tetraisopropoxide, titanium ethoxide, zirconium tetraisopropoxide, and aluminum trisisopropoxide.

[0027] When a polyvalent acid metal salt is obtained by the above method, the polyvalent acid ion may be the ion of the above-mentioned polyvalent acid. When the polyvalent acid metal salt is added to the aqueous medium, the polyvalent acid itself may be added, or a water-soluble polyvalent acid metal salt may be added to the aqueous medium and dissociated in the aqueous medium.

[0028] As described above, the presence of polyvalent acid metal salt particles on the surface of the toner particles promotes the transfer of charges inside and outside the toner particles, thereby making it possible to suppress overcharging. However, in order to effectively realize this overcharging suppression effect, it is necessary that a certain proportion or more of small-diameter polyvalent acid metal salt particles are present.

[0029] In the present invention, the presence of a certain proportion or more of small-diameter polyvalent acid metal salt particles suppresses overcharging.

[0030] When the total volume of polyvalent metal salt particles is constant, small-diameter polyvalent metal salt particles have a larger contact area with the toner matrix than large-diameter polyvalent metal salt particles. Therefore, when a certain proportion of small-diameter polyvalent metal salt particles is present, the conductive path between the polyvalent metal salt particles and the toner matrix increases, allowing the charge inside the toner to be smoothly transferred to the toner surface.

[0031] In addition, the small particle size of the polyvalent metal salt particles increases the contact area between the polyvalent metal salt particles in the toner particles, and thus promotes the transfer of electric charges between the toner particles. 2When the area ratio of the polyvalent metal salt particles is 0.3% or more and 16.0% or less, the number of small polyvalent metal salt particles is optimal for forming a sufficient conductive path, and as a result, it is believed that overcharging is suppressed.

[0032] On the other hand, as mentioned above, in order to improve solid printing performance, it is necessary to develop a force that can more actively transport the toner to the developing member, and this cannot be achieved by simply controlling the proportion of small-diameter polyvalent acid metal salt particles.

[0033] In the present invention, the proportion of large-diameter polyvalent metal salt particles is at least a certain level, thereby increasing the toner supplying power and achieving improved solid printing performance.

[0034] It is believed that gradient force is involved in the increase in the toner supply force in the present invention. Gradient force is a force that acts on a conductor when the conductor is present in an electric field, and electrostatic polarization occurs inside the conductor due to the electric field, and a force acts in the direction in which the electric field is stronger by the difference in the strength of the electric field between the location where a positive charge is generated and the location where a negative charge is generated. In the present invention, when a voltage is applied to a developing member such as a developing roller, an electric field is formed around the developing member. It is believed that the electric field generates electrostatic polarization in the polyvalent acid metal particles, which are conductors, and a gradient force acts on the polyvalent acid metal particles in the direction of the developing member.

[0035] In particular, when the polyvalent acid metal salt particles contain a metal element included in Groups 3 to 13 as in the present invention, a polarity difference between the metal element and the polyvalent acid is likely to occur, and the polarization in the polyvalent acid metal salt particles is large, so that the gradient force in the electric field can be strengthened. In order to further strengthen the gradient force, it is preferable that the Pauling electronegativity of the metal element is 1.30 or more and 1.60 or less. Examples include titanium (Group 4, electronegativity: 1.54) and zirconium (Group 4, electronegativity: 1.33). When the electronegativity of the metal element is within the above range, in addition to suppressing moisture absorption, a polarity difference with the polyvalent acid is likely to occur, and the polarization in the polyvalent acid metal salt is large, so that the gradient force in the electric field can be further strengthened.

[0036] The Pauling electronegativity was determined from the value given in "Chemical Handbook: Basics, 5th Revised Edition, Maruzen Publishing, edited by the Chemical Society of Japan (2004)."

[0037] The gradient force F is given by the relative dielectric constant ε r In the case of a sphere, it is known that the following equation (6) can be expressed. F = 2πε0{(ε r -2) / (ε r +2)}a 3 Grade E 2 (6)

[0038] Here, ε0 is the dielectric constant of a vacuum, gradE is the gradient of the electric field, and a is the radius of the conductive particle.

[0039] According to formula (6), the larger the radius a of the conductive particle, the stronger the gradient force.

[0040] Thus, the larger the particle diameter of the conductive fine particles, the stronger the gradient force. When the above formula (2) is satisfied, the number of large-diameter polyvalent metal salt particles is sufficiently large, and the gradient force works effectively. As a result, it is believed that the supply of toner to the developing member is sufficiently increased, and solid followability is improved. Thus, in order to improve the gradient force, a certain proportion of large-diameter polyvalent metal salt particles is necessary.

[0041] To summarise the above mechanisms, it is believed that the presence of a certain number of small-sized polyvalent metal salt particles and a certain number of large-sized polyvalent metal salt particles each provides the effects of both suppressing overcharging, mainly through the small-sized polyvalent metal salt particles, and improving solid print conformability through the large-sized polyvalent metal salt particles.

[0042] Furthermore, as an effect of using small-diameter polyvalent metal salt particles and large-diameter polyvalent metal salt particles in combination, when a certain amount or more of large-diameter polyvalent metal salt particles are present between the small-diameter polyvalent metal salt particles, the polyvalent metal salt particles present on the surface of each toner particle are interdigitated with each other, increasing the conductive path between the toner particles. In particular, by satisfying formulas (1) and (2), the ratio of the number of small-diameter polyvalent metal salt particles to the number of large-diameter polyvalent metal salt particles becomes optimal, and it is considered that interdigitation is likely to occur.

[0043] In addition, when formulas (1) and (2) are satisfied, the unevenness of the toner surface caused by the particle size difference of the polyvalent acid metal salt particles causes the developing roller, which is an elastic body, to deform, and the contact area with the toner surface increases, which is thought to increase the conductive path between the toner and the developing roller, also contributing to the suppression of overcharging.

[0044] The toner of the present invention will be described in detail below.

[0045] <Surface condition of toner particles> The toner of the present invention is a toner having toner particles containing a binder resin, wherein polyvalent acid metal salt particles of a polyvalent acid and a compound containing at least one metal element selected from the metal elements included in Groups 3 to 13 are present on the surface of the toner particles, and in a backscattered electron image of the toner taken at a magnification of 50,000 times using a scanning electron microscope, the area of ​​the polyvalent acid metal salt particles relative to the total number of the polyvalent acid metal salt particles is 100 nm 2 The following number ratio (%) is A, the area of ​​the polyvalent acid metal salt particles is 500 nm 2 When the percentage (%) of the number of particles is B, the following formulas (1) and (2) are satisfied, and in the backscattered electron image, an area of ​​100 nm2 is smaller than the total area of ​​the toner particle surface in the observed field of view. 2 The area ratio of the polyvalent acid metal salt particles is 0.3% or more and 16.0% or less. It is also preferable that the above B satisfies the following formula (7). 83.0≦A (1) 1.7≦B≦17.0 (2) 1.7≦B≦10.0 (7)

[0046] By satisfying the above formula (1), the proportion of small-diameter polyvalent metal salt particles is sufficiently large, and a sufficient conductive path is formed. By satisfying the above formula (2), the proportion of large-diameter polyvalent metal salt particles is sufficiently large, and the effect of the gradient force is enhanced, and detachment of the polyvalent metal salt particles from the substrate surface caused by the presence of an excess of large-diameter polyvalent metal salt particles and the resulting contamination of components can be suppressed. Furthermore, when the area is less than 100 nm 2 By making the area ratio of the polyvalent acid metal salt particles below 0.3% or more, a sufficient amount of polyvalent acid metal salt particles can be present on the toner particle surface to realize the effects obtained by the above formulas (1) and (2). 2 By making the area ratio of the polyvalent acid metal salt particles 16.0% or less, it is possible to suppress component contamination due to detachment of the polyvalent acid metal salt particles from the toner particle surface and charging defects due to leakage caused by the formation of excessive conductive paths.

[0047] In addition, the above A, B and area 100 nm 2 The area ratio of the polyvalent acid metal salt particles described below can be controlled by the production method such as the amount of raw materials when the polyvalent acid metal salt particles are attached to the toner base particles and the alcohol concentration in the system. The production method will be described later.

[0048] The toner of the present invention has a backscattered electron image of the toner taken at a magnification of 50,000 times using a scanning electron microscope, in which the area of ​​the polyvalent acid metal salt particles relative to the total number of the polyvalent acid metal salt particles is 100 nm 2 More than 500nm 2 When the following number ratio (%) is taken as C, it is preferable that the following formula (3) is satisfied, and it is more preferable that the following formula (8) is satisfied. 3.0 <C≦15.3 (3) 4.0 <C≦15.3 (8)

[0049] Area 100nm 2 More than 500nm 2The following polyvalent metal salt particles contribute to both the formation of a conductive path and the expression of gradient force, so when the above formula (3) is satisfied, the area is 100 nm 2 More than 500nm 2 The number of polyvalent acid metal salt particles is optimal, and it becomes easier to achieve both the effect of the present invention of suppressing overcharging and improving solid conformability.

[0050] In the toner of the present invention, the average area of ​​the polyvalent acid metal salt particles is 10 nm 2 More than 5000nm 2 Preferably, it is 14 nm or less. 2 More than 3000nm 2 It is more preferable that the average area of ​​the polyvalent acid metal salt particles is 10 nm or less. 2 By setting the average area of ​​the polyvalent metal salt particles to 5000 nm or more, the sum of the gradient forces acting on the polyvalent metal salt particles present on the toner surface becomes large, making it easier to achieve solid coverage. 2 By keeping the surface area of ​​contact with the toner matrix and the organosilicon polymer described below sufficiently large, the polyvalent acid metal salt particles can be prevented from migrating from the toner particle surface to other members. Also, disturbance of the electric field around the developing member due to contamination of the member can be suppressed, and a decrease in the effect of the gradient force can be prevented.

[0051] The average area of ​​the polyvalent acid metal salt particles can be controlled by controlling the proportion of coarse particles in the production method, or by the temperature at which the polyvalent acid metal salt particles are produced.

[0052] In the toner of the present invention, the coefficient of variation of the area of ​​the polyvalent metal salt particles is preferably 10.0 or less, more preferably 8.0 or less. When the coefficient of variation of the area of ​​the polyvalent metal salt particles is 10.0 or less, the polyvalent metal salt particles are highly dispersible, and a good conductive path is easily formed. In addition, the variation in the charge amount of the polyvalent metal salt particles is reduced, so that a gradient force acts on the entire toner particles, and the effect of improving the solid followability is further enhanced.

[0053] The coefficient of variation of the area of ​​the polyvalent acid metal salt particles can be controlled by the production method, such as the production rate of the polyvalent acid metal salt particles.

[0054] In the toner of the present invention, in a backscattered electron image of the toner taken at a magnification of 50,000 times using a scanning electron microscope, the ratio of the area of ​​the polyvalent acid metal salt particles to the total area of ​​the toner particle surface in the observed field of view is preferably 1.1% or more and 26.3% or less, and more preferably 1.1% or more and 13.1% or less.

[0055] By making the area ratio of the polyvalent metal salt particles 1.1% or more, the absolute amount of small-sized polyvalent metal salt particles that mainly contribute to suppressing overcharging and large-sized polyvalent metal salt particles that contribute to improving solid conformability increases, and the effects of suppressing overcharging and improving solid conformability are significantly manifested. Also, by making the area ratio of the polyvalent metal salt particles 13.1% or less, detachment of the polyvalent metal salt particles from the base surface and the resulting contamination of components can be suppressed.

[0056] The ratio of the area of ​​the polyvalent acid metal salt particles to the total area of ​​the toner particle surface can be controlled by the input amounts of raw materials, etc.

[0057] The toner of the present invention preferably satisfies the following formula (4), and more preferably satisfies the following formula (9), when the average height in the normal direction of the polyvalent acid metal salt particles is taken as Ha (nm) in a mapping analysis using an energy dispersive X-ray spectrometer (EDS) on the cross section of the toner particle observed under a transmission electron microscope (TEM). 2.5≦Ha≦50.0 (4) 10.0≦Ha≦40.0 (9)

[0058] When Ha is 2.5 or more, the polyvalent metal salt particles present on the surface of each toner tend to be bitten by each other, and a conductive path tends to be formed between the toners, which results in a large effect of suppressing overcharging. Also, when Ha is 50.0 or less, the polyvalent metal salt particles are too high and tend to apply shear to the surface during durability, which can prevent the polyvalent metal salt particles from coming off the base surface, thereby suppressing contamination of components.

[0059] In the toner of the present invention, when a metal element contained in the polyvalent acid metal salt particles is defined as a metal element M, the amount of metal of the metal element M contained in the toner determined by X-ray fluorescence analysis is defined as M1 (detection intensity kcps), 1.0 g of the toner is dispersed in a mixed aqueous solution consisting of 31.0 g of a 61.5 mass % sucrose aqueous solution and 6.0 g of a 10 mass % aqueous neutral detergent for cleaning precision measuring instruments, which is composed of a nonionic surfactant, an anionic surfactant, and an organic builder, and the toner is obtained by subjecting the toner to a process (a) of shaking 300 times per minute using a shaker for 20 minutes, and the amount of metal of the metal element M contained in the toner (a) determined by X-ray fluorescence analysis is defined as M2 (detection intensity kcps), it is preferable that M1 and M2 satisfy the following formula (5), and more preferably satisfy formula (10). 0.85≦M2 / M1 (5) 0.90≦M2 / M1 (10)

[0060] By satisfying formula (5), detachment of polyvalent acid metal salt particles from the toner particle surface is reduced throughout long-term durability, and contamination of components can be suppressed. In addition, the effects of suppressing overcharging and improving solid-color conformability can be achieved through long-term use.

[0061] The value of M2 can be controlled by controlling the adhesive strength of the polyvalent acid metal salt particles to the toner particle surface through the production method, the amount of organosilicon polymer added, and the like.

[0062] The materials contained in the toner of the present invention will be described in detail below.

[0063] <Organosilicon polymers and organosilicon compounds> The toner of the present invention preferably has an organosilicon compound on the surface of the toner particles, and the compound is preferably an organosilicon polymer.

[0064] The organosilicon polymer used in the present invention is not particularly limited and may be any conventionally known organic polymer. Among them, it is preferable to use an organosilicon polymer having a partial structure represented by formula (11). R-SiO 3 / 2 Formula (11) (In formula (11), R represents an alkyl group, an alkenyl group, an acyl group, an aryl group, or a methacryloxyalkyl group.)

[0065] The above formula (11) indicates that the organosilicon polymer has an organic group and a silicon polymer portion. As a result, the organosilicon polymer containing the partial structure represented by the above formula (11) is strongly bonded to the toner base particles because the organic group has affinity with the toner base particles, and is strongly bonded to the polyvalent acid metal salt because the silicon polymer portion has affinity with the polyvalent acid metal salt. In this way, the polyvalent acid metal salt can be more strongly bonded to the toner base particles through the organosilicon polymer.

[0066] In addition, when the metal element belongs to Groups 3 to 13, the valence of the metal element is 2 or more, and it can form a crosslinked structure with the organosilicon compound, so that a crosslinked structure with the polymer of the organosilicon compound can be formed on the toner particle surface. This crosslinked structure suppresses the migration of the polyvalent acid metal salt particles to the developing member, and promotes the transfer of charges on the toner surface and between toner particles, thereby enhancing the effect of suppressing overcharging.

[0067] Furthermore, the organosilicon compound bridges the polyvalent acid metal salt particles, forming a network of the organosilicon compound and the polyvalent acid metal salt particles on the surface of the toner particles. The polyvalent acid metal salt particles have high thermal conductivity, so they can quickly transfer the heat of the fixing device to the toner during fixing, but when the above network is present, the heat received by a part of the toner particles can be quickly transferred to the entire particle surface. In particular, small-diameter polyvalent acid metal salt particles are widely dispersed on the toner particles and contribute greatly to network formation, so that the presence of a certain number or more of them has a high effect of improving fixing properties. From the viewpoint of achieving both the expression of the above effect and the suppression of fixing deterioration due to high coating of the organosilicon compound, the content of the organosilicon compound is preferably 0.3 parts by mass or more and 20.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or polymerizable monomer.

[0068] The organosilicon compound for obtaining the organosilicon polymer can be any conventionally known organosilicon compound without any particular limitation, and is preferably at least one organosilicon compound selected from the group consisting of organosilicon compounds represented by the following formula (12): R-Si-(Ra)3Equation (12) (In formula (12), each Ra independently represents a halogen atom or an alkoxy group, and each R independently represents an alkyl group, an alkenyl group, an aryl group, an acyl group, or a methacryloxyalkyl group.)

[0069] Specific examples of the silane compound represented by formula (12) include trifunctional methylsilane compounds such as methyltrimethoxysilane, methyltriethoxysilane, methyldiethoxymethoxysilane, and methylethoxydimethoxysilane; trifunctional silane compounds such as ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, hexyltrimethoxysilane, and hexyltriethoxysilane; and trifunctional phenylsilane compounds such as phenyltrimethoxysilane and phenyltriethoxysilane. trifunctional vinyl silane compounds such as vinyltrimethoxysilane and vinyltriethoxysilane; trifunctional allyl silane compounds such as allyltrimethoxysilane, allyltriethoxysilane, allyldiethoxymethoxysilane and allylethoxydimethoxysilane; trifunctional γ-methacryloxypropyl silane compounds such as γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropyldiethoxymethoxysilane and γ-methacryloxypropylethoxydimethoxysilane; and trifunctional silane compounds such as γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropyldiethoxymethoxysilane and γ-methacryloxypropylethoxydimethoxysilane.

[0070] <Binding resin> The toner of the present invention contains a binder resin.

[0071] As the binder resin, any conventionally known resin can be used without any particular limitation. Specific examples include vinyl resins, polyester resins, polyurethane resins, and polyamide resins. Polymerizable monomers that can be used to manufacture vinyl resins include styrene monomers such as styrene and α-methylstyrene; acrylic acid esters such as methyl acrylate and butyl acrylate; methacrylic acid esters such as methyl methacrylate, 2-hydroxyethyl methacrylate, t-butyl methacrylate, and 2-ethylhexyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated dicarboxylic acids such as maleic acid; unsaturated dicarboxylic anhydrides such as maleic anhydride; nitrile vinyl monomers such as acrylonitrile; halogen-containing vinyl monomers such as vinyl chloride; and nitro vinyl monomers such as nitrostyrene.

[0072] Among them, it is preferable that the binder resin contains a vinyl resin or a polyester resin.

[0073] <Coloring agent> The toner of the present invention may contain a colorant. As the colorant, there is no particular limitation, and conventionally known pigments and dyes of black, yellow, magenta, cyan, and other colors, magnetic materials, and the like can be used.

[0074] Black colorants include black pigments such as carbon black.

[0075] Examples of yellow colorants include yellow pigments and yellow dyes such as monoazo compounds, disazo compounds, condensed azo compounds, isoindolinone compounds, benzimidazolone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds.

[0076] Specific examples include CI Pigment Yellow 74, 93, 95, 109, 111, 128, 155, 174, 180, and 185, and CI Solvent Yellow 162.

[0077] Examples of magenta colorants include magenta pigments and magenta dyes such as monoazo compounds, condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds.

[0078] Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, 269, and CI Pigment Violet Red 19.

[0079] Examples of cyan colorants include cyan pigments and cyan dyes such as copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, and basic dye lake compounds.

[0080] Specifically, examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66.

[0081] The content of the colorant is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or the polymerizable monomer.

[0082] The toner may also contain a magnetic material to make it a magnetic toner.

[0083] In this case, the magnetic material can also serve as a colorant.

[0084] Examples of magnetic materials include iron oxides such as magnetite, hematite, and ferrite; metals such as iron, cobalt, and nickel; and alloys of these metals with metals such as aluminum, cobalt, copper, lead, magnesium, tin, zinc, antimony, beryllium, bismuth, cadmium, calcium, manganese, selenium, titanium, tungsten, and vanadium, and mixtures thereof.

[0085] <Wax> The toner of the present invention may contain a wax. As the wax, any conventionally known wax may be used without any particular limitation. Specifically, there are esters of monohydric alcohols and monocarboxylic acids, such as behenyl behenate, stearyl stearate, and palmityl palmitate; esters of dihydric carboxylic acids and monoalcohols, such as dibehenyl sebacate; esters of dihydric alcohols and monocarboxylic acids, such as ethylene glycol distearate and hexanediol dibehenate; esters of trihydric alcohols and monocarboxylic acids, such as glycerin tribehenate; esters of tetrahydric alcohols and monocarboxylic acids, such as pentaerythritol tetrastearate and pentaerythritol tetrapalmitate; dipentaerythritol hexastearate and dipentaerythritol hexastearate. Examples of such waxes include esters of hexahydric alcohols such as tall hexapalmitate and monocarboxylic acids; esters of polyfunctional alcohols such as polyglycerin behenate and monocarboxylic acids; natural ester waxes such as carnauba wax and rice wax; petroleum-based hydrocarbon waxes and their derivatives such as paraffin wax, microcrystalline wax, and petrolatum; hydrocarbon waxes and their derivatives produced by the Fischer-Tropsch process; polyolefin-based hydrocarbon waxes and their derivatives such as polyethylene wax and polypropylene wax; higher aliphatic alcohols; fatty acids such as stearic acid and palmitic acid; and acid amide waxes.

[0086] From the viewpoint of releasability, the content of the wax is preferably from 1.0 to 30.0 parts by mass, and more preferably from 5.0 to 20.0 parts by mass, relative to 100.0 parts by mass of the binder resin or polymerizable monomer.

[0087] <Charge control agent> The toner of the present invention may contain a charge control agent within a range that does not inhibit the expression of gradient force and charge control by the polyvalent acid metal salt particles. As the charge control agent, any known charge control agent can be used without any particular limitation.

[0088] Specific examples of the negative charge control agent include metal compounds of aromatic carboxylic acids such as salicylic acid, alkylsalicylic acid, dialkylsalicylic acid, naphthoic acid, and dicarboxylic acids, or polymers or copolymers having metal compounds of the aromatic carboxylic acids; polymers or copolymers having a sulfonic acid group, a sulfonate salt group, or a sulfonate ester group; metal salts or metal complexes of azo dyes or azo pigments; boron compounds, silicon compounds, and calixarenes.

[0089] On the other hand, examples of the positive charge control agent include the following: quaternary ammonium salts, polymeric compounds having quaternary ammonium salts in the side chains, guanidine compounds, nigrosine compounds, imidazole compounds, etc. As the polymer or copolymer having a sulfonate group or a sulfonate ester group, a homopolymer of a sulfonate group-containing vinyl monomer such as styrene sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-methacrylamido-2-methylpropanesulfonic acid, vinylsulfonic acid, or methacrylsulfonic acid, or a copolymer of the vinyl monomer shown in the section on binder resin and the above-mentioned sulfonate group-containing vinyl monomer, etc. can be used.

[0090] The content of the charge control agent is preferably 0.01 parts by mass or more and 5.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or polymerizable monomer.

[0091] <External additives> Toner particles having an organosilicon polymer on the surface thereof exhibit excellent properties such as flowability even in the absence of external additives, but may contain external additives for further improvement.

[0092] As the external additive, there is no particular limitation and any external additive known in the art can be used.

[0093] Specific examples of the silica fine particles include: raw silica fine particles such as wet-process silica and dry-process silica, and silica fine particles obtained by subjecting such raw silica fine particles to a surface treatment with a treating agent such as a silane coupling agent, a titanium coupling agent, or silicone oil; and resin fine particles such as vinylidene fluoride fine particles and polytetrafluoroethylene fine particles.

[0094] The content of the external additive is preferably 0.1 parts by mass or more and 5.0 parts by mass or less with respect to 100.0 parts by mass of the toner particles.

[0095] Next, a method for obtaining the toner of the present invention will be described in detail below.

[0096] <Method of manufacturing toner base particles> The method for producing the toner base particles (the toner particles before the polyvalent acid metal salt particles are attached are also referred to as "toner base particles") is not particularly limited, and a suspension polymerization method, a solution suspension method, an emulsion aggregation method, a pulverization method, etc. can be used.

[0097] As an example, a method for obtaining toner base particles by suspension polymerization will be described below.

[0098] First, a polymerizable monomer capable of forming a binder resin and, if necessary, various additives are mixed, and the materials are dissolved or dispersed using a disperser to prepare a polymerizable monomer composition.

[0099] The various additives include colorants, waxes, charge control agents, polymerization initiators, chain transfer agents, and the like.

[0100] Examples of the dispersing machine include a homogenizer, a ball mill, a colloid mill, and an ultrasonic dispersing machine.

[0101] Next, the polymerizable monomer composition is added to an aqueous medium containing poorly water-soluble inorganic fine particles, and droplets of the polymerizable monomer composition are prepared using a high-speed disperser such as a high-speed stirrer or an ultrasonic disperser (granulation process).

[0102] Thereafter, the polymerizable monomer in the droplets is polymerized to obtain toner base particles (polymerization step).

[0103] The polymerization initiator may be mixed when the polymerizable monomer composition is prepared, or may be mixed into the polymerizable monomer composition immediately before forming droplets in the aqueous medium.

[0104] Alternatively, the compound may be added in a state dissolved in the polymerizable monomer or in another solvent, as required, during or after the granulation of the droplets, that is, immediately before the start of the polymerization reaction.

[0105] After obtaining a binder resin by polymerizing the polymerizable monomer, a solvent removal treatment may be carried out as necessary to obtain a dispersion liquid of toner base particles.

[0106] When the binder resin is obtained by the emulsion aggregation method or the suspension polymerization method, the polymerizable monomer may be any conventionally known monomer without any particular limitation. Specifically, the vinyl monomers listed in the section on the binder resin may be used.

[0107] As the polymerization initiator, any known polymerization initiator can be used without any particular limitation. Specific examples thereof include the following.

[0108] Hydrogen peroxide, acetyl peroxide, cumyl peroxide, tert-butyl peroxide, propionyl peroxide, benzoyl peroxide, chlorobenzoyl peroxide, dichlorobenzoyl peroxide, bromomethylbenzoyl peroxide, lauroyl peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, diisopropyl peroxycarbonate, tetralin hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide, pertriphenylacetic acid-tert-hydroperoxide, tert-butyl performate, tert-butyl peracetate, tert-butyl perbenzoate, tert-butyl perphenylacetate, tert-butyl permethoxyacetate, per-N-(3-tolyl)palmitate-tert-butylbenzoyl peroxide, t-butyl peroxybenzoyl peroxide, Examples of the polymerization initiator include peroxide-based polymerization initiators such as butyl peroxy 2-ethylhexanoate, t-butyl peroxy pivalate, t-butyl peroxy isobutyrate, t-butyl peroxy neodecanoate, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide; and azo- or diazo-based polymerization initiators such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile.

[0109] <Method of Adhering Polyvalent Metal Salt Particles> Examples of methods for adhering polyvalent acid metal salt particles to toner base particles include a method in which a metal compound serving as a metal source is reacted with a polyvalent acid ion in an aqueous medium in which toner particles are dispersed to obtain polyvalent acid metal salt particles, and a method in which polyvalent acid metal salt particles are adhered to toner particles by mechanical external force in a dry or wet manner.

[0110] (1) A method in which a metal compound serving as a metal source is reacted with a polyvalent acid ion in an aqueous medium in which toner base particles are dispersed to obtain a polyvalent acid metal salt.

[0111] For example, a compound containing a metal element and a polyacid are added to a dispersion liquid of toner base particles and mixed to cause a reaction between the compound containing a metal element and the polyacid, and the reactant is precipitated. At the same time, the dispersion liquid is stirred to cause the reactant to adhere to the toner base particles.

[0112] (2) A method in which polyvalent acid metal salt particles are attached to the surface of toner base particles by mechanical external force in a dry or wet manner.

[0113] For example, a high-speed agitator that applies shear force to powder or aqueous medium, such as an FM Mixer, Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.), Super Mixer, Nobilta (manufactured by Hosokawa Micron Corporation), or TK Homo Mixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), is used to apply a force that disintegrates the polyvalent acid metal salt particles, causing the polyvalent acid metal salt particles to adhere to the toner base particles.

[0114] Among them, a method of obtaining a polyvalent acid metal salt by reacting a metal compound as a metal source with a polyvalent acid ion in an aqueous medium in which toner base particles are dispersed is preferred. By using the above method, it is possible to uniformly disperse the polyvalent acid metal salt on the toner particle surface. As a result, a conductive path is efficiently formed, and overcharging can be suppressed with fewer polyvalent acid metal salt particles. Furthermore, the uniform dispersion of the polyvalent acid metal salt particles allows a gradient force to act uniformly on the toner particle surface, improving solid followability.

[0115] When the above method is used, the area of ​​polyvalent metal salt particles observed with a scanning electron microscope is 100 nm 2 The percentage of the number of particles below 100 nm 2 More than 500nm 2 The percentage of the number of particles below, area 500 nm 2 The above number ratio, area ratio of polyvalent acid metal salt particles, average area of ​​polyvalent acid metal salt particles, coefficient of variation of area of ​​polyvalent acid metal salt particles, height of polyvalent acid metal salt particles, and difficulty of polyvalent acid metal salt particles falling off from the toner base particles can be easily adjusted within the range of the present invention.

[0116] More specifically, the reaction can be controlled by the amount of the compound containing a metal element added during the reaction between the polyvalent acid and the compound containing a metal element, the alcohol concentration in the toner base particle dispersion, the temperature, the pH, the addition rate of the compound containing a metal element, and the amount of the organosilicon compound added.

[0117] A more preferred method for producing the toner having the configuration of the present invention is to produce polyvalent acid metal salt particles from a compound containing at least one metal element selected from the metal elements included in groups 3 to 13 and a polyvalent acid in an aqueous medium, and adjust the concentration of the alcohol having 1 to 10 carbon atoms in the aqueous medium to 0.0% by mass or more and 0.35% by mass or less, more preferably 0.20% by mass or less.

[0118] If alcohol is present in the system when polyvalent acid metal salt particles are generated, the polyvalent acid metal salt particles and the alcohol form hydrogen bonds in the system, and the polyvalent acid metal salt particles are stably dispersed in water. This effect is particularly noticeable for polyvalent acid metal salt particles on the large particle size side. Therefore, if there is a lot of alcohol in the system, it becomes difficult to generate polyvalent acid metal salt particles with a large particle size. By setting the concentration of alcohol with 1 to 10 carbon atoms in the system to 0.35 mass % or less, it is possible to obtain polyvalent acid metal salt particles with an area of ​​100 nm 2 While maintaining a certain amount of polyvalent metal salt particles below 500 nm 2 The number of the above polyvalent acid metal salt particles can be increased.

[0119] In addition, according to the above method, the polyvalent acid metal salt particles generated in the aqueous medium are attached to the toner base particles before the growth is completed, so that the polyvalent acid metal salt particles are more strongly fixed to the toner base particles than when pre-prepared polyvalent acid metal salt particles are attached by mechanical external force. As a result, the polyvalent acid metal salt particles do not separate from the base particles even during long-term use, and a toner with excellent durability can be obtained that can exhibit the effects of the present invention, which are suppression of overcharging and improvement of solid followability.

[0120] In addition, it is more preferable to introduce an organosilicon compound into the aqueous medium at the same time as the reaction of the metal compound with the polyvalent acid ion, and to react the organosilicon compound in the aqueous medium to obtain an organosilicon polymer.By using the above method, the polyvalent acid metal salt particles generated in the aqueous medium are fixed more firmly to the toner particle surface by the organosilicon polymer before they grow, so that it is possible to further increase the dispersibility of the polyvalent acid metal salt particles.In addition, the polyvalent acid metal salt particles are firmly fixed to the toner particle by the organosilicon polymer, so that the effect of improving the durability described above is more remarkable.In addition, the interface area between the toner base particle and the polyvalent acid metal salt is widened, so that the transfer of electric charge is promoted, and the effect of suppressing overcharging is increased.

[0121] As the metal compound, polyacid and organosilicon compound used in the above method, the above-mentioned metal compound, polyacid and organosilicon compound can be used, respectively.

[0122] <Method of attaching organosilicon compounds> The method for adhering the organosilicon compound to the toner base particles will be exemplified below.

[0123] The method for adhering the organosilicon compound of the present invention is not particularly limited, and a conventionally known method can be used. For example, a method of condensing the compound shown in the above-mentioned organosilicon compound section in an aqueous medium in which toner base particles are dispersed, and adhering the organosilicon compound onto the toner base particles, or a method of adhering the organosilicon compound onto the toner base particles by mechanical external force in a dry or wet manner can be mentioned.

[0124] Among these, a method in which a compound shown in the above section on organosilicon compounds is condensed in an aqueous medium in which toner base particles are dispersed, and the organosilicon compound is then adhered to the toner base particles, is preferred, since this method makes it possible to firmly adhere the organosilicon compound to the toner base particles and to uniformly adhere the organosilicon compound to the toner base particles.

[0125] The above method will be described below.

[0126] When the organosilicon compound is attached to the toner base particles by the above method, it is preferable to include a step (step 1) of dispersing the toner base particles in an aqueous medium to obtain a toner base particle dispersion, and a step (step 2) of mixing an organosilicon compound (or a hydrolyzate thereof) with the toner base particle dispersion and subjecting the organosilicon compound to a condensation reaction in the toner base particle dispersion to attach the organosilicon compound to the toner base particles. Furthermore, in order to adjust the amount of alcohol in the toner base particle dispersion involved in the formation of polyvalent acid metal salt particles, the method may include a step (step 3) of removing alcohol from the hydrolyzate of the organosilicon compound, as necessary.

[0127] In the above step 1, the method for obtaining the toner base particle dispersion may include a method of using the dispersion of toner base particles produced in an aqueous medium as is, and a method of putting dried toner base particles into an aqueous medium and dispersing them mechanically, etc. When dispersing dried toner base particles in an aqueous medium, a dispersion aid may be used.

[0128] As the dispersion aid, known dispersion stabilizers and surfactants can be used. Specifically, the dispersion stabilizer includes inorganic dispersion stabilizers such as tricalcium phosphate, hydroxyapatite, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silica, and alumina, and organic dispersion stabilizers such as polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch. In addition, the surfactant includes anionic surfactants such as alkyl sulfate ester salts, alkylbenzene sulfonates, and fatty acid salts, nonionic surfactants such as polyoxyethylene alkyl ethers and polyoxypropylene alkyl ethers, and cationic surfactants such as alkylamine salts and quaternary ammonium salts. Among them, it is preferable to include an inorganic dispersion stabilizer, and it is more preferable to include a dispersion stabilizer containing a phosphate such as tricalcium phosphate, hydroxyapatite, magnesium phosphate, zinc phosphate, or aluminum phosphate.

[0129] In the above step 2, the organosilicon compound may be added to the toner base particle dispersion liquid as it is, or may be added to the toner base particle dispersion liquid after hydrolysis. Among them, it is preferable to add it after hydrolysis, since the condensation reaction is easy to control and the amount of the organosilicon compound remaining in the toner base particle dispersion liquid can be reduced. The above hydrolysis is preferably carried out in an aqueous medium whose pH is adjusted using a known acid and base. It is known that the hydrolysis of an organosilicon compound is pH-dependent, and it is preferable to appropriately change the pH when carrying out the above hydrolysis depending on the type of the organosilicon compound. For example, when methyltriethoxysilane is used as the organosilicon compound, it is preferable that the pH of the above aqueous medium is 2.0 or more and 6.0 or less.

[0130] Specific examples of acids for adjusting the pH include inorganic acids such as hydrochloric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, hypobromous acid, bromous acid, bromic acid, perbromic acid, hypoiodous acid, iodous acid, iodic acid, periodic acid, sulfuric acid, nitric acid, phosphoric acid, and boric acid, and organic acids such as acetic acid, citric acid, formic acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid.

[0131] Specific examples of bases for adjusting the pH include the following: alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, lithium hydroxide, etc., and aqueous solutions of these; alkali metal carbonates such as potassium carbonate, sodium carbonate, lithium carbonate, etc., and aqueous solutions of these; alkali metal sulfates such as potassium sulfate, sodium sulfate, lithium sulfate, etc., and aqueous solutions of these; alkali metal phosphates such as potassium phosphate, sodium phosphate, lithium phosphate, etc., and aqueous solutions of these; alkaline earth metal hydroxides such as calcium hydroxide, magnesium hydroxide, etc., and aqueous solutions of these; and amines such as ammonia and triethylamine.

[0132] The condensation reaction in the step 2 is preferably controlled by adjusting the pH of the toner base particle dispersion. It is known that the condensation reaction of an organosilicon compound is pH-dependent, and the pH at which the condensation reaction is carried out is preferably changed as appropriate depending on the type of organosilicon compound. For example, when methyltriethoxysilane is used as the organosilicon compound, the pH of the aqueous medium is preferably 6.0 or more and 12.0 or less. As the acid and base for adjusting the pH, the acids and bases exemplified in the above hydrolysis section can be used.

[0133] The condensation reaction in step 2 is preferably carried out at a temperature of about 10°C or higher and 100°C or lower.

[0134] The method used in the above step 3 is not particularly limited, and examples of the method include a method of separating the hydrolyzate of the organosilicon compound and the alcohol by vacuum distillation utilizing the difference in boiling points between them, and a method of separating the alcohol by adsorption onto a porous material capable of adsorbing alcohol, such as zeolite. Among these, the method of separating the alcohol by vacuum distillation is preferred, since it allows a high degree of freedom in adjusting the alcohol removal conditions and allows easy adjustment of the amount of alcohol removed.

[0135] When removing alcohol by the above method, the optimal temperature depends on the organosilicon compound used. For example, when methyltriethoxysilane is used, it is preferable to carry out the process at a temperature of 20°C or higher and 50°C or lower in order to simultaneously inhibit condensation of the organosilicon compound and promote dealcoholization.

[0136] The optimum reduced pressure conditions in the above method depend on the type of organosilicon compound used. For example, when methyltriethoxysilane is used, it is preferable to carry out the method at -90 kPa or more and -50 kPa or less in order to separate only the alcohol.

[0137] Next, the measurement methods used in the present invention will be described in detail below. In the description of each measurement method, the toner, toner particles, or toner base particles will also be referred to as "toner, etc."

[0138] <Method of observing the surface of toner, etc.> The surface of the toner, etc. is observed as follows.

[0139] Using a scanning electron microscope (SEM, device name: JSM-7800F manufactured by JEOL Ltd.), the surface of the toner, etc. is observed at a magnification of 50,000 times. Then, using EDX (energy dispersive X-ray spectroscopy), mapping of elements on the surface of the toner, etc. is performed. From the obtained SEM element mapping image, the presence of an organosilicon compound, a reaction product between a polyvalent acid and a compound containing the above-mentioned metal element on the surface of the toner, etc. is confirmed.

[0140] Specifically, by comparing the mapping image of the metal element with the mapping image of an element contained in the polyacid (for example, phosphorus when phosphoric acid is used as the polyacid), and finding that the two images match, it can be confirmed that the sample contains a reaction product of a compound containing a metal element and a polyacid.

[0141] <Calculation method for number ratio, area ratio, average area, and coefficient of variation for each area range of polyvalent acid metal salt particles, and number average particle size of organosilicon polymer fine particles and polyvalent acid metal salt fine particles> The number ratio, area ratio, average area, and coefficient of variation for each area range of the polyvalent acid metal salt particles, as well as the number average particle size of the organosilicon polymer fine particles and polyvalent acid metal salt fine particles, are calculated as follows.

[0142] (1) Sample preparation A thin layer of conductive paste (TED PELLA, Inc., Product No. 16053, PELCO Colloidal Graphite, Isopropanol base) was applied to the sample stage (aluminum sample stage), and toner or the like was sprayed on top of it. Excess sample was then removed from the sample stage using air blowing to prepare the sample.

[0143] (2) Observation using JSM-7800F SEM images (backscattered electron images) were taken using the above-mentioned JSM-7800F. The observation conditions are described below.

[0144] Start the "PC-SEM" of the JSM-7800F, insert the sample holder into the sample chamber of the JSM-7800F housing, and move the sample holder to the observation position. On the PC-SEM screen, set the accelerating voltage to [1.0 kV] and the observation magnification to [50,000x]. Press the [ON] button of the observation icon to apply the accelerating voltage and observe the backscattered electron image.

[0145] (3) Calculation of the number ratio, area ratio, average area, and coefficient of variation for each area range of polyvalent acid metal salt particles The obtained backscattered electron image was loaded into the image processing and analysis software "ImageJ", and after averaging, binarization was performed to obtain a binarized image in which the polyvalent acid metal salt particles or the organosilicon polymer particles were displayed in white. The obtained binarized image was then loaded into the image processing and analysis software "Image-Pro Plus", and the number ratio, area ratio, average area value, and coefficient of variation of the polyvalent acid metal salt particles per areal range, or the number average particle size of the organosilicon polymer particles and the polyvalent acid metal salt particles were obtained using the built-in functions. The above processing was performed for 10 fields of view of the backscattered electron image observed at 50,000x magnification, and the arithmetic average value of the 10 fields of view was used as the number ratio, area ratio, average area value, and coefficient of variation of the polyvalent acid metal salt particles per areal range, and the number average particle size of the organosilicon polymer particles and the polyvalent acid metal salt particles.

[0146] <Method for measuring height Ha of polyvalent metal salt particles in the normal direction> The cross section of the toner, etc. is observed by the following method using a transmission electron microscope (TEM). First, the toner, etc. is thoroughly dispersed in a room temperature curing epoxy resin, and then cured for 2 days in an atmosphere of 40°C. A 100 nm thick flake-like sample is cut out from the obtained cured product using a microtome equipped with a diamond blade. This sample is magnified 100,000 times with a TEM (trade name: electron microscope Tecnai TF20XT, manufactured by FEI), and the cross section of the toner, etc. is observed. In this case, the cross section of the toner, etc. is selected to have a major axis diameter of 0.9 to 1.1 times the number average particle diameter (D1) of the toner, etc. measured according to the measurement method of the number average particle diameter (D1) of the toner, etc. described later.

[0147] Next, the constituent elements of the cross section of the obtained toner, etc. are analyzed using energy dispersive X-ray spectroscopy (EDX) to create an EDX mapping image.

[0148] In the EDX mapping image, a signal derived from the polyvalent acid metal salt particle is confirmed on the outline of the cross section of the toner or the like, and the height Ha of the polyvalent acid metal salt particle in the normal direction is determined.

[0149] The cross sections of 50 toner particles or the like are observed by the above method, the height (nm) of the polyvalent acid metal salt particles in the normal direction is measured from the image, and the arithmetic average value of the 50 particles is taken as Ha (nm).

[0150] <Calculation method for adhesion rate of polyvalent metal salt particles in toner, etc.> The adhesion rate of the polyvalent acid metal salt particles is calculated by the following method.

[0151] A process for removing weakly adhered polyvalent metal salt particles from toner, etc. (Process (a)) Add 160 g of sucrose (Kishida Chemical Co., Ltd.) to 100 mL of ion-exchanged water and dissolve it in a hot water bath to prepare a 61.5% by mass sucrose aqueous solution. Add 31.0 g of the above sucrose concentrated solution and 6 g of Contaminon N (trade name) (a 10% by mass aqueous solution of a neutral detergent for cleaning precision measuring instruments, pH 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) to a centrifuge tube to prepare a dispersion. Add 1.0 g of toner, etc. to this dispersion, and break up clumps of toner, etc. with a spatula, etc. The centrifuge tube is shaken in a shaker at 300 spm (strokes per minute) for 20 minutes. After shaking, the solution is transferred to a glass tube (50 mL) for a swing rotor and separated in a centrifuge at 3500 rpm for 30 minutes. Visually check that the toner, etc. and the aqueous solution are sufficiently separated, and collect the toner, etc. that has separated to the top layer with a spatula, etc. After filtering the collected toner, etc. with a vacuum filter, dry it in a dryer for at least one hour. Crush the dried product with a spatula to obtain the toner, etc. (a).

[0152] (2) Measurement and calculation method of adhesion rate The amount of metal originating from the polyvalent acid metal salt particles contained in the toner or the like before and after the above-mentioned treatment (a) is determined by a fluorescent X-ray analyzer.

[0153] The detection intensity of metals contained in toner, etc. was measured by the following method.

[0154] The detection intensity of metals contained in toner, etc. is measured using a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical) for setting measurement conditions and analyzing measurement data.

[0155] The anode of the X-ray tube is Rh, the measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 27 mm, and the measurement time is 10 seconds.

[0156] In addition, when measuring light elements, a proportional counter (PC) is used, and when measuring heavy elements, a scintillation counter (SC) is used.

[0157] As a measurement sample, 4 g of toner or the like (a) that has been subjected to the above treatment (a) is placed in a dedicated aluminum ring for pressing and flattened. After that, using a tablet molding compression machine "BRE-32" (manufactured by Maekawa Test Machinery Manufacturing Co., Ltd.), pressure is applied at 20 MPa for 60 seconds to form pellets with a thickness of 2 mm and a diameter of 39 mm. The above operation is also carried out on toner or the like before the above treatment (a) is also formed into pellets. For each sample, the detection intensity (unit: cps) of metal and silicon observed at a diffraction angle (2θ) = 109.08° when pentaerythritol (PET) is used as the analyzing crystal is measured. In this case, the acceleration voltage and current value of the X-ray generator are set to 24 kV and 100 mA, respectively.

[0158] In the X-ray fluorescence analysis, the amount of metal contained in the polyvalent acid metal salt particles before the treatment (a) is M1 (detection intensity kcps), and the amount of metal contained in the polyvalent acid metal salt particles after the treatment (a) is M2 (detection intensity kcps), and the adhesion rate is calculated using the following formula. Adhesion rate of polyvalent metal salt particles = M2 / M1

[0159] <Method of measuring weight average particle size (D4) and number average particle size (D1)> The weight average particle diameter (D4) and number average particle diameter (D1) of the toner or the like are calculated as follows.

[0160] The measuring device used is a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube.

[0161] The measurement conditions are set and the measurement data is analyzed using the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (Beckman Coulter, Inc.). The measurement is performed with an effective measurement channel count of 25,000 channels.

[0162] The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of 1.0%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.).

[0163] Before performing measurements and analysis, the dedicated software is set up as follows.

[0164] In the "Change standard measurement method (SOMME)" screen of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard particle 10.0 μm" (Beckman Coulter, Inc.). Press the "Threshold / Noise level measurement button" to automatically set the threshold and noise level. In addition, set the current to 1,600 μA, the gain to 2, the electrolyte to ISOTON II, and check "Flush aperture tube after measurement."

[0165] In the "Pulse to particle size conversion setting" screen of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range from 2 μm to 60 μm.

[0166] The specific measurement method is as follows. (1) Pour 200.0 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture tube flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Place 30.0 mL of the electrolyte solution in a 100 mL flat-bottom glass beaker. Add 0.3 mL of a solution of "Contaminon N" (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion-exchanged water as a dispersant. (3) Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetra150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. Place 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank and add 2.0 mL of Contaminon N to this tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is being irradiated with ultrasonic waves, 10 mg of toner or the like is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted so that it is between 10°C and 40°C. (6) Using a pipette, drip the electrolytic solution (5) in which the toner or the like has been dispersed into the round-bottom beaker (1) placed in the sample stand to adjust the measurement concentration to 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device to calculate the weight average particle size (D4) and number average particle size (D1). When the dedicated software is set to Graph / Volume %, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight average particle size (D4). When the dedicated software is set to Graph / Number %, the "Average diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen is the number average particle size (D1).

[0167] <Method for measuring alcohol concentration in aqueous media> The alcohol concentration in the aqueous medium when the polyvalent acid metal salt particles are formed and when the polyvalent acid metal salt particles are attached to the toner surface is measured by gas chromatography in the following manner.

[0168] The polymerization reaction liquid (slurry) is filtered using a membrane filter (e.g., Advantec Toyo Co., Ltd., Disposable Membrane Filter 25JP020AN), and 2 μL of the filtrate is analyzed by gas chromatography. Then, the alcohol concentration in the aqueous medium is measured using a calibration curve previously prepared using the corresponding alcohol. The analysis was performed under the following conditions.

[0169] <Analysis conditions> GC:HP 6890GC Column: HP INNOWax (200 μm × 0.40 μm × 50 m) Carrier gas: He (constant flow mode, initial flow rate: 1.00 ml / min, average linear velocity: 25 cm / sec) Oven: 50℃: hold for 10 minutes, heat to 200℃ at 10℃ / min, hold at 200℃ for 5 minutes. INJ: 200℃, split mode (pressure: 32.8psi, split flow rate: 30.0ml / min, total flow rate: 33.5ml / min) Split ratio: 30.1:1.0 DET: 250℃ (FID) EXAMPLES

[0170] The present invention will be described in detail with reference to the following examples. However, the present invention is not limited to these examples. The toner and the method for producing the toner will be described below. In the examples and comparative examples, "parts" are all based on mass unless otherwise specified.

[0171] <Production Example of Toner Base Particle Dispersion> <Production Example of Toner Base Particle Dispersion 1> (Preparation of aqueous medium) 14.0 parts of sodium phosphate (12-hydrate) (manufactured by Rasa Kogyo Co., Ltd.) was added to a reaction vessel containing 390.0 parts of ion-exchanged water, and the mixture was kept at 65°C for 1.0 hour while purging with nitrogen. An aqueous calcium chloride solution in which 9.2 parts of calcium chloride (dihydrate) was dissolved in 10.0 parts of ion-exchanged water was added all at once to the reaction vessel while stirring at 12,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), to prepare an aqueous medium containing a dispersion stabilizer.

[0172] Furthermore, 1.0 mol / L of hydrochloric acid was added to the aqueous medium in the reaction vessel to adjust the pH to 6.0, thereby preparing aqueous medium 1.

[0173] (Preparation of Polymerizable Monomer Composition) Styrene 60.0 parts CI Pigment Red 122 5.9 parts CI Pigment Red 150 3.4 parts The above materials were placed in an attritor (manufactured by Nippon Coke & Engineering Co., Ltd.), and further dispersed using zirconia particles having a diameter of 1.7 mm at 220 rpm for 5.0 hours to prepare a colorant dispersion in which the pigment was dispersed.

[0174] The following materials were then added to the colorant dispersion: Styrene 10.0 parts 30.0 parts n-butyl acrylate Polyester resin 5.0 parts (condensation polymer of terephthalic acid and 2 moles of propylene oxide adduct of bisphenol A) Fischer-Tropsch wax (melting point 70°C) 7.0 parts The above materials were kept at 65° C. and uniformly dissolved and dispersed at 500 rpm using a TK homomixer to prepare a polymerizable monomer composition.

[0175] (granulation process) While maintaining the temperature of the aqueous medium 1 at 70° C. and the rotation speed of the stirring device at 12,000 rpm, the polymerizable monomer composition was charged into the aqueous medium 1, and 9.0 parts of t-butyl peroxypivalate as a polymerization initiator was added. Granulation was continued for 10 minutes while maintaining the stirring device at 12,000 rpm.

[0176] (Polymerization process) The high-speed stirring device was changed to a stirrer equipped with a propeller stirring blade, and polymerization was carried out for 5.0 hours while maintaining 70°C with stirring at 150 rpm, and then the temperature was raised to 85°C and heated for 2.0 hours to carry out the polymerization reaction. Ion-exchanged water was added to adjust the toner base particle concentration in the dispersion to 20.0%, and toner base particle dispersion 1 in which toner base particles 1 are dispersed was obtained.

[0177] The toner base particles 1 had a number average particle size (D1) of 6.0 μm and a weight average particle size (D4) of 6.4 μm.

[0178] <Production Example of Toner Base Particle Dispersion Liquid 2> (Preparation of Polyester 1) Into a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube, a dehydration tube, and a pressure reducing device, 85.0 parts of terephthalic acid, 16.4 parts of trimellitic anhydride, 123.3 parts of bisphenol A, and 14.1 parts of ethylene glycol were added and heated to a temperature of 128°C with stirring.

[0179] After adding 0.5 parts of titanium (IV) isopropoxide as an esterification catalyst, the mixture was heated to 158° C. and subjected to condensation polymerization for 5 hours. The mixture was then heated to 180° C. and subjected to reaction under reduced pressure until a desired molecular weight was obtained, thereby obtaining polyester 1.

[0180] (Preparation of styrene-acrylic resin 1) Into a reaction vessel equipped with a stirrer, a thermometer, and a nitrogen inlet tube, 80.0 parts of styrene, 20.0 parts of n-butyl acrylate, and 0.3 parts of hexanediol diacrylate were added and heated to a temperature of 80° C. with stirring.

[0181] Subsequently, 2.0 parts of Perbutyl O (10-hour half-life temperature 72.1° C. (manufactured by NOF Corp.)) was added as a polymerization initiator, and polymerization was continued for 5 hours to obtain styrene-acrylic resin 1.

[0182] (Preparation of Toner Base Particles 2) Polyester 1 89.0 parts Styrene-acrylic resin 1 13.0 parts CI Pigment Blue 15:3 (copper phthalocyanine) 5.2 parts Ester wax (behenyl behenate: melting point 72°C) 15.0 parts Fischer-Tropsch wax (Sasol C105, melting point: 105°C) 2.0 parts The above materials were premixed in a Mitsui Henschel mixer (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and then melt-kneaded using a twin-screw extruder (product name: PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) with the temperature set so that the molten temperature at the discharge outlet was 140°C.

[0183] The obtained kneaded product was cooled, coarsely pulverized with a hammer mill, and then finely pulverized with a pulverizer (product name: Turbo Mill T250, manufactured by Turbo Kogyo Co., Ltd.) The obtained finely pulverized powder was classified with a multi-division classifier utilizing the Coanda effect to obtain toner base particles 2.

[0184] The toner base particles 2 had a number average particle size (D1) of 5.7 μm and a weight average particle size (D4) of 6.6 μm.

[0185] (Preparation of aqueous medium) To a reaction vessel containing 390.0 parts of ion-exchanged water, 14.0 parts of sodium phosphate (12-hydrate) (manufactured by Rasa Kogyo Co., Ltd.) were added, and the mixture was kept at 65° C. for 1.0 hour while being purged with nitrogen.

[0186] While stirring at 12,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), an aqueous calcium chloride solution prepared by dissolving 9.2 parts of calcium chloride (dihydrate) in 10.0 parts of ion-exchanged water was added all at once to a reaction vessel to prepare an aqueous medium containing a dispersion stabilizer.

[0187] Furthermore, 1.0 mol / L of hydrochloric acid was added to the aqueous medium in the reaction vessel to adjust the pH to 6.0, thereby preparing an aqueous medium.

[0188] (Preparation of toner base particle dispersion 2) 200.0 parts of toner base particles 2 were added to the aqueous medium and dispersed for 15 minutes while rotating at 5000 rpm using a TK homomixer at a temperature of 60° C. Ion-exchanged water was added to adjust the toner particle concentration in the dispersion to 20.0%, and toner base particle dispersion 2 was obtained.

[0189] <Production Example of Toner Base Particle Dispersion 3> (Preparation of Resin Particle Dispersion) The following materials were weighed, mixed and dissolved: Styrene 82.6 parts n-Butyl acrylate 9.2 parts Acrylic acid 1.3 parts Hexanediol diacrylate 0.4 parts n-Lauryl mercaptan 3.2 parts A 10% aqueous solution of NEOGEN RK (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added to this solution and dispersed, and an aqueous solution of 0.15 parts of potassium persulfate dissolved in 10.0 parts of ion-exchanged water was added while slowly stirring for another 10 minutes.

[0190] After replacing with nitrogen, emulsion polymerization was carried out for 6.0 hours at a temperature of 70° C. After the polymerization was completed, the reaction liquid was cooled to room temperature, and ion-exchanged water was added to obtain a resin particle dispersion liquid with a solid content concentration of 12.5% ​​and a number average particle size of 0.2 μm.

[0191] (Preparation of Colorant Particle Dispersion) The following materials were weighed and mixed: Ester wax (melting point 70°C) 100.0 parts · 15.0 parts of Neogen RK Ion-exchanged water 385.0 parts Disperse the wax particles for 1 hour using a wet jet mill JN100 (manufactured by Jokou Co., Ltd.). A dispersion liquid was obtained. The solid content concentration of the wax particle dispersion liquid was 20.0%.

[0192] The following materials were weighed and mixed: CI Pigment Red 122 62.6 parts CI Pigment Red 150 37.4 parts · 15.0 parts of Neogen RK Ion-exchanged water 885.0 parts The mixture was dispersed for 1 hour using a wet jet mill JN100 to obtain a colorant particle dispersion. The solids concentration of the particle dispersion was 10.0%.

[0193] (Preparation of Toner Base Particles 3) ·Resin particle dispersion liquid 160.0 parts Wax particle dispersion 10.0 parts Colorant particle dispersion 18.9 parts Magnesium sulfate 0.2 parts The above materials were dispersed using a homogenizer (IKA), and then heated to 65°C while stirring. After stirring at 65°C for 1.0 hour, it was confirmed by observation with an optical microscope that aggregate particles with a number-average particle size of 5.9 μm had been formed. After adding 2.2 parts of NEOGEN RK (Dai-ichi Kogyo Seiyaku Co., Ltd.), the temperature was raised to 80°C and stirred for 2.0 hours to obtain fused colored resin particles.

[0194] After cooling, the mixture was filtered, and the filtered solid was washed with 720.0 parts of ion-exchanged water by stirring for 1.0 hour. The dispersion liquid containing the colored resin was filtered and then dried to obtain toner base particles 3.

[0195] The toner base particles 3 had a number average particle size (D1) of 6.1 μm and a weight average particle size (D4) of 7.0 μm.

[0196] (Preparation of aqueous medium) To a reaction vessel containing 390.0 parts of ion-exchanged water, 14.0 parts of sodium phosphate (12-hydrate) (manufactured by Rasa Kogyo Co., Ltd.) were added, and the mixture was kept at 65° C. for 1.0 hour while being purged with nitrogen.

[0197] A calcium chloride aqueous solution in which 9.2 parts of calcium chloride (dihydrate) was dissolved in 10.0 parts of ion-exchanged water was added all at once while stirring at 12,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to prepare an aqueous medium containing a dispersion stabilizer.

[0198] Furthermore, 1.0 mol / L of hydrochloric acid was added to the aqueous medium in the reaction vessel to adjust the pH to 6.0, thereby preparing an aqueous medium.

[0199] (Preparation of toner base particle dispersion 3) 100.0 parts of toner base particles 3 were added to the aqueous medium and dispersed for 15 minutes while rotating at 5000 rpm using a TK homomixer at a temperature of 60° C. Ion-exchanged water was added to adjust the solid content of toner base particles 3 in the dispersion to 20.0%, thereby obtaining toner base particle dispersion 3.

[0200] <Production Example of Toner Base Particle Dispersion Liquid 4> (Preparation of emulsified slurry) 660.0 parts of ion-exchanged water and 25.0 parts of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate were mixed and stirred, and the mixture was stirred at 10,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to prepare an aqueous medium.

[0201] The following materials were added to 500.0 parts of ethyl acetate and dissolved at 100 rpm using a propeller stirrer to prepare a solution. Styrene / butyl acrylate copolymer 100.0 parts (Copolymerization mass ratio: 80 / 20) Polyester resin 3.0 parts (Condensation polymer of terephthalic acid and 2 moles of propylene oxide adduct of bisphenol A) CI Pigment Red 122 6.1 parts CI Pigment Red 150 3.5 parts Fischer-Tropsch wax (melting point 70°C) 9.0 parts

[0202] Next, 150.0 parts of the above aqueous medium was placed in a vessel and stirred at 12,000 rpm using a TK homomixer, and 100.0 parts of the above solution was added thereto and mixed for 10 minutes to prepare an emulsified slurry.

[0203] (Preparation of Toner Base Particles 4) Thereafter, 100.0 parts of the emulsified slurry was placed in a flask equipped with a degassing pipe, a stirrer, and a thermometer, and the solvent was removed under reduced pressure at 30°C for 12 hours while stirring at a peripheral speed of 20 m / min, and then aged at 45°C for 4 hours to obtain a solvent-free slurry.

[0204] The solvent-removed slurry was filtered under reduced pressure, and then 300.0 parts of ion-exchanged water was added to the resulting filter cake, which was then mixed and redispersed in a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), and then filtered.

[0205] The obtained filter cake was dried in a dryer at 45° C. for 48 hours, and sieved through a mesh with an opening of 75 μm to obtain toner base particles 4.

[0206] The toner base particles 4 had a number average particle size (D1) of 5.6 μm and a weight average particle size (D4) of 6.8 μm.

[0207] (Preparation of aqueous medium) To a reaction vessel containing 390.0 parts of ion-exchanged water, 14.0 parts of sodium phosphate (12-hydrate) (manufactured by Rasa Kogyo Co., Ltd.) were added, and the mixture was kept at 65° C. for 1.0 hour while being purged with nitrogen.

[0208] Using a TK homomixer, while stirring at 12000 rpm, an aqueous calcium chloride solution in which 9.2 parts of calcium chloride (dihydrate) was dissolved in 10.0 parts of ion-exchanged water was added all at once to prepare an aqueous medium containing a dispersion stabilizer. Furthermore, 1.0 mol / L of hydrochloric acid was added to the aqueous medium to adjust the pH to 6.0, and an aqueous medium was prepared.

[0209] (Preparation of Toner Base Particle Dispersion 4) 100.0 parts of toner base particles 4 were added to the aqueous medium and dispersed for 15 minutes while rotating at 5000 rpm using a TK homomixer at a temperature of 60° C. Ion-exchanged water was added to adjust the solid content of toner base particles 4 in the dispersion to 20.0%, thereby obtaining toner base particle dispersion 4.

[0210] <Production Example of Organosilicon Compound Liquid> <Production Examples of Organosilicon Compound Liquids 1 and 2> 70.0 parts of ion-exchanged water Methyltriethoxysilane 30.0 parts The above materials were weighed into a 200 mL beaker, and the pH was adjusted to 3.5 with 10% hydrochloric acid. Then, the mixture was stirred for 1.0 hour while adjusting the temperature to 30°C in a water bath to produce organosilicon compound liquid 1. Then, the produced organosilicon compound liquid 1 was subjected to reduced pressure distillation at 40°C and -90 kPa for 2.0 hours to obtain organosilicon compound liquid 2 from which a portion of the ethanol contained in organosilicon compound liquid 1 was removed.

[0211] <Production Example of Organosilicon Compound Liquid 3> Ion-exchanged water 90.0 parts Methyltrimethoxysilane (organic silicon compound) 10.0 parts The above materials were mixed, and 1.0 mol / L of hydrochloric acid was added to adjust the pH to 4.0. After that, the mixture was stirred for 1 hour while being heated to 60° C. in a water bath, to prepare organosilicon compound liquid 3.

[0212] <Production Example of Organosilicon Compound Particles> <Production Example of Organosilicon Polymer Particle 1> 1620 parts of water was placed in a vessel equipped with a stirrer and heated to 70°C in a warm bath, after which 1.0 mol / L sodium hydroxide solution was added to adjust the pH to 9.0. 33.0 parts of the above organosilicon compound liquid 1 was added over 1 hour, and the mixture was kept at 70°C for 1 hour to carry out condensation polymerization. After that, 0.1 mol / L sodium hydroxide solution was gradually added to adjust the pH to 10.5, and condensation polymerization was carried out at 70°C for another 3 hours to obtain a dispersion of organosilicon polymer particles 1.

[0213] The resulting dispersion of organosilicon polymer fine particles 1 was centrifuged to remove coarse particles, and then filtered, washed and dried to obtain organosilicon polymer particles 1.

[0214] The number average particle size of the organosilicon polymer particles 1 was 30 nm.

[0215] <Production Example of Polyvalent Acid Metal Salt Particles> <Polyvalent acid metal salt particles 1> Ion-exchanged water 100.0 parts Sodium phosphate (12-hydrate) [Rasa Kogyo Co., Ltd.] 8.5 parts After mixing the above, 16.0 parts (corresponding to 7.0 parts of titanium lactate) of 44% aqueous solution (TC-310: manufactured by Matsumoto Fine Chemical Co., Ltd.) was added while stirring at 12,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) at 85 ° C. The pH was adjusted to 7.5 by adding 1 mol / L hydrochloric acid.

[0216] The solids were then separated by centrifugation. The process of dispersing again in ion-exchanged water and separating the solids by centrifugation was repeated three times to remove ions such as sodium. The particles were dispersed again in ion-exchanged water and dried by spray drying to obtain titanium phosphate compound microparticles with a number-average particle size of 8.0 nm, which were designated as polyvalent acid metal salt particles 1.

[0217] <Polyvalent acid metal salt particles 2> Polyvalent acid metal salt particles 2 having a number average particle size of 166 nm were obtained in the same manner as in Production Example 1 of polyvalent acid metal salt particles 1, except that the temperature was changed to 40°C.

[0218] <Polyvalent acid metal salt particles 3> Polyvalent acid metal salt particles 3 having a number average particle size of 18.5 nm were obtained in the same manner as in Production Example 1 of polyvalent acid metal salt particles 1, except that the temperature was changed to 60°C.

[0219] <Toner manufacturing example> <Toner 1 Manufacturing Example> 500.0 parts of toner base particle dispersion 1 was weighed out and placed in a reaction vessel, and stirred using a propeller stirring blade.

[0220] Next, 1.0 mol / L hydrochloric acid was added to adjust the pH of the mixed solution to 5.5, and immediately after that, 8.0 parts of the organosilicon compound liquid 2 was added, and then ethanol (Kishida Chemical Co., Ltd.) was added so that the ethanol concentration of the mixed solution became 0.02 mass%. Then, the pH was adjusted to 9.5 using 1.0 mol / L NaOH aqueous solution.

[0221] Next, the temperature of the mixed solution was increased to 55° C., and the following materials were then added to the mixed solution all at once. Titanium lactate 44% aqueous solution 2.44 parts (TC-310: Matsumoto Fine Chemical Co., Ltd., equivalent to 1.07 parts of titanium lactate)

[0222] The mixture was then held for 1 hour while being mixed using a propeller impeller, and the pH was adjusted to 9.5 using a 1.0 mol / L NaOH aqueous solution, and the temperature was kept at 55° C. while being stirred for 2 hours.

[0223] After the temperature was lowered to 25° C., the pH was adjusted to 1.5 with 1.0 mol / L hydrochloric acid and stirred for 1 hour, and then the mixture was filtered while being washed with ion-exchanged water to obtain toner particles 1. This was named toner 1.

[0224] As a result of the analysis, it was confirmed that Toner 1 had a reaction product (in the form of fine particles) of phosphoric acid and a compound containing titanium, and an organosilicon compound, on the surface.

[0225] In addition, in a reflected electron image of the toner, the area of ​​the polyvalent acid metal salt particles relative to the total number of the polyvalent acid metal salt particles is 100 nm 2 The percentage of the number of the following particles (%) is 86.2%, and the area of ​​the polyvalent acid metal salt particles is 500 nm 2 The percentage of the above particles was 9.8%. Furthermore, in the backscattered electron image, the area of ​​100 nm 2 The area ratio of the following polyvalent acid metal salt particles was 3.6%.

[0226] The reaction product of phosphoric acid and a compound containing titanium is a reaction product of titanium lactate (a compound containing titanium) and sodium phosphate or phosphate ions (polyacid) derived from calcium phosphate in an aqueous medium.

[0227] <Production examples of toners 5-29, 32-36> In the production example of toner 1, toner particles 5-29 and 32-36 were obtained by changing the production conditions to those shown in Table 1. Toner particles 5-29 and 32-36 were used as toners 5-29 and 32-36.

[0228] <Toner 3 Manufacturing Example> The following materials were weighed and placed in a reaction vessel, and stirred using a propeller stirring blade. Toner base particle dispersion 1 500.0 parts Organosilicon polymer particles 1 3.0 parts

[0229] Next, ethanol (Kishida Chemical Co., Ltd.) was added so that the ethanol concentration in the mixed solution was 0.02% by mass, and then the pH was adjusted to 9.5 using a 1.0 mol / L NaOH aqueous solution.

[0230] Next, the temperature of the mixed solution was increased to 55° C., and the following materials were then added to the mixed solution all at once. Titanium lactate 44% aqueous solution 2.44 parts (TC-310: Matsumoto Fine Chemical Co., Ltd., equivalent to 1.07 parts of titanium lactate)

[0231] The mixture was then held for 1 hour while being mixed using a propeller impeller, and the pH was adjusted to 9.5 using a 1.0 mol / L NaOH aqueous solution, and the temperature was kept at 55° C. while being stirred for 2 hours.

[0232] After the temperature was lowered to 25° C., the pH was adjusted to 1.5 with 1.0 mol / L hydrochloric acid and the mixture was stirred for 1 hour, and then the mixture was filtered while being washed with ion-exchanged water to obtain toner particles 3. This was named toner 3.

[0233] <Toner 4 Manufacturing Example> 500.0 parts of toner base particle dispersion 1 was weighed out and placed in a reaction vessel, and stirred using a propeller stirring blade.

[0234] Next, 1.0 mol / L hydrochloric acid was added to adjust the pH of the mixed solution to 5.5, and immediately after that, 8.0 parts of the organosilicon compound liquid 2 was added. Then, the pH was adjusted to 9.5 using 1.0 mol / L NaOH aqueous solution. Immediately after adjusting the pH, the following materials were added to the mixed solution. Polyvalent metal salt particles 1 0.43 parts Polyvalent metal salt particles 2 0.05 parts Polyvalent metal salt particles 3 0.02 parts

[0235] The temperature of the mixture was then raised to 55°C, and the mixture was held for 1 hour while being mixed using a propeller agitator. The pH was then adjusted to 9.5 using a 1.0 mol / L NaOH aqueous solution, and the mixture was held at 55°C for 2 hours while being stirred.

[0236] After the temperature was lowered to 25° C., the pH was adjusted to 1.5 with 1.0 mol / L hydrochloric acid and the mixture was stirred for 1 hour, and then the mixture was filtered while being washed with ion-exchanged water to obtain toner particles 4. This is toner 4.

[0237] <Toner 30 manufacturing example> In the production example of toner 4, the type and number of parts of the polyvalent acid metal salt particles to be added were changed as follows to obtain toner particles 30. Toner particles 30 are designated as toner 30. Polyvalent metal salt particles 1 0.42 parts Polyvalent metal salt particles 2 0.08 parts

[0238] <Toner 31 Manufacturing Example> In the production example of toner 4, the amount of the polyvalent acid metal salt fine particles to be added was changed to the following parts to obtain toner particles 31. Toner particles 31 are designated as toner 31. Polyvalent metal salt particles 1 0.49 parts Polyvalent metal salt particles 2 0.01 parts Polyvalent metal salt particles 3 0.002 parts

[0239] <Toner 2 Manufacturing Example> 500.0 parts of toner base particle dispersion 1 was weighed out and placed in a reaction vessel, and stirred using a propeller stirring blade.

[0240] Next, 1.0 mol / L hydrochloric acid was added to adjust the pH of the mixed solution to 5.5, and immediately thereafter 8.0 parts of the organosilicon compound liquid 2 was added. After that, the pH was adjusted to 9.5 using a 1.0 mol / L NaOH aqueous solution.

[0241] The temperature of the mixture was then raised to 55°C, and the mixture was held for 1 hour while being mixed using a propeller agitator. The pH was then adjusted to 9.5 using a 1.0 mol / L NaOH aqueous solution, and the mixture was held at 55°C for 2 hours while being stirred.

[0242] After the temperature was lowered to 25° C., the pH was adjusted to 1.5 with 1.0 mol / L hydrochloric acid and stirred for 1 hour, and then the mixture was washed with ion-exchanged water and filtered to obtain toner particles 2. Thereafter, the following materials were added to a SUPERMIXER PICCOLO SMP-2 (manufactured by Kawata Corporation). Toner particles 2 100.0 parts Polyvalent metal salt particles 1 0.43 parts Polyvalent metal salt particles 2 0.05 parts Polyvalent metal salt particles 3 0.02 parts

[0243] After mixing at 3000 rpm for 20 minutes, the mixture was sieved through a mesh having an opening of 150 μm to obtain Toner 2.

[0244] [Table 1]

[0245] Comparative toner manufacturing example <Production Example of Comparative Toner 1> The toner base particle dispersion 1 was filtered and dried to obtain the toner base particles 1 which were taken out and used as they are as toner particles 37 .

[0246] Toner particles 37 100.0 parts Titanium oxide particles (volume average particle size 23 nm) 0.50 parts Organosilicon polymer fine particles 1 3.0 parts The above materials were charged into a SUPERMIXER PICCOLO SMP-2 (manufactured by Kawata Corporation) and mixed at 3000 rpm for 20 minutes, after which the mixture was sieved through a mesh with 150 μm openings to obtain Comparative Toner 1.

[0247] <Production Examples of Comparative Toners 2 to 5> In the production example of toner 1, the production conditions were changed to those shown in Table 2 to produce toner particles 38 to 41, which were used as comparative toners 2 to 5.

[0248] <Production Example of Comparative Toner 6> The following materials were weighed and placed in a reaction vessel and mixed using a propeller stirring blade. Titanium lactate 44% aqueous solution 0.75 parts (TC-310: Matsumoto Fine Chemical Co., Ltd., equivalent to 0.33 parts of titanium lactate) Toner base particle dispersion 1 500.0 parts

[0249] Next, 1.0 mol / L hydrochloric acid was added to adjust the pH of the mixed solution to 5.5, and immediately thereafter 20.0 parts of organosilicon compound liquid 3 was added, and the pH was adjusted to 7.0 using 1.0 mol / L aqueous NaOH solution.

[0250] After the temperature of the mixture was raised to 50°C, it was held for 1 hour while being mixed using a propeller agitator. Thereafter, the pH was adjusted to 9.5 using a 1.0 mol / L NaOH aqueous solution, and the temperature was held at 50°C while being stirred for 2 hours.

[0251] After the temperature was lowered to 25° C., the pH was adjusted to 1.5 with 1.0 mol / L hydrochloric acid and the mixture was stirred for 1 hour, and then the mixture was filtered while being washed with ion-exchanged water to obtain toner particles 42. This was designated as comparative toner 6.

[0252] In the comparative toner 6, the ethanol concentration in the polyvalent acid metal salt particle generation system is as high as 0.35%, and therefore the area of ​​the generated polyvalent acid metal salt particles is 500 nm 2 The percentage of items with the above characteristics was low at 1.2%.

[0253] [Table 2]

[0254] The physical properties of Toners 1 to 36 and Comparative Toners 1 to 6 are shown in Table 3.

[0255] [Table 3]

[0256] The symbols (A) to (L) in Table 3 represent the following: (A) Metal elements contained in polyvalent acid metal salt particles (B) Polyvalent acid contained in polyvalent acid metal salt particles (C) Area of ​​polyvalent acid metal salt particles: 100 nm 2 The percentage of the following items (%) (D) Area of ​​polyvalent acid metal salt particles: 500 nm 2 Percentage of items above (%) (E) Area 100nm 2 The area ratio (%) of the polyvalent acid metal salt particles is as follows: (F) Area of ​​polyvalent acid metal salt particles: 100 nm 2 More than 500nm 2 The percentage of the following items (%) (G) Average area of ​​polyvalent metal salt particles (nm 2 ) (H) Coefficient of variation of the area of ​​polyvalent metal salt particles (I) Area ratio of polyvalent acid metal salt particles (%) (J) The average height of the polyvalent metal salt particles in the normal direction is Ha (nm). (K) Adhesion rate M2 / M1 (L) Presence or absence of organosilicon compounds on the toner particle surface

[0257] [Examples 1 to 36, Comparative Examples 1 to 6] The above toners 1 to 36 and comparative toners 1 to 6 were evaluated by the methods described below. The evaluation results are shown in Table 4.

[0258] The evaluation method and evaluation criteria of the present invention will be described below.

[0259] <Evaluation of solid color conformity> A modified version of a commercially available Canon laser beam printer, the LBP7600C, was used.

[0260] The modification involved changing the gears and software of the evaluation machine itself, so that the rotational speed of the developing roller was set to 2.2 times the peripheral speed of the drum. In addition, the toner supply roller was removed. 40 g of toner was loaded into the toner cartridge of the LBP7600C. In a normal temperature and humidity environment (temperature 25°C / relative humidity 50%), a LETTER size Business 4200 paper (Xerox, 75 g / m 2 ) five solid images were printed.

[0261] The solid image was evaluated for its solid followability.

[0262] The image density was measured using a Macbeth Reflection Densitometer RD918 (manufactured by Macbeth) in accordance with the attached instruction manual by measuring the relative density of the image in the white background area with an image density of 0.00, and the obtained relative density was used as the image density value.

[0263] (Evaluation criteria for solid tracking ability) The evaluation was made based on the difference in image density between the leading edge of the first all-solid image and the trailing edge of the third all-solid image. A: The difference between the image density at the leading edge of the first full solid image and the image density at the trailing edge of the third full solid image is less than 0.10. B: The difference between the image density of the leading edge of the first solid image and the image density of the trailing edge of the third solid image is 0.10 or more and less than 0.20 C: The difference between the image density of the leading edge of the first all-solid image and the image density of the trailing edge of the third all-solid image is 0.20 or more and less than 0.30 D: The difference between the image density of the leading edge of the first solid image and the image density of the trailing edge of the third solid image is 0.30 or more.

[0264] <Evaluation of suppression of overcharging> As the image forming apparatus, the following modified laser printer and process cartridge were used. A commercially available laser printer, LBP-7700C (Canon Inc.), modified to have a process speed of 250 mm / sec. - Toner Cartridge 323 (Black), a commercially available process cartridge (manufactured by Canon Inc.) The product toner was removed from the inside of the cartridge, and after cleaning with an air blower, 150 g of the toner to be evaluated was filled in. The product toner was removed from each of the yellow, magenta, and cyan stations, and the yellow, magenta, and cyan cartridges with the toner remaining amount detection mechanism disabled were inserted and evaluated.

[0265] The above process cartridge, the above modified laser printer, and the following transfer paper were left to stand for 48 hours in a low temperature and low humidity environment (temperature 0° C. / relative humidity 10%). Transfer paper: GF-C081 (Canon Inc., A4: 81.4 g / m 2 ) In a low temperature environment, 10,000 images with a printing rate of 0.5% were printed on transfer paper in succession. After that, the amount of printing was 0.20 mg / cm 2 One halftone image was printed, and the image was visually observed to check for unevenness in density. At the same time, the surface of the developing roller was visually observed to check the state of the toner layer on the developing roller. The performance of suppressing overcharging was evaluated based on the following evaluation criteria.

[0266] Overcharging is likely to occur in low temperature and low humidity environments. When overcharging occurs, the adhesion between the toner and the developing roller increases, making it difficult to regulate with the regulating blade. As a result, the toner layer on the developing roller becomes thicker, which may cause density unevenness on the image. In the case of a toner that is excellent in suppressing overcharging, it is possible to obtain a good image even under the above conditions.

[0267] (Evaluation criteria for suppressing overcharging) A: The toner layer on the developing roller is uniform, and there is no unevenness in the density of the image. It is very good at suppressing overcharging. B: The toner layer on the developing roller is slightly thicker at the edges, but the image has no uneven density. It has excellent suppression of overcharging. C: The toner layer on the developing roller is somewhat uneven overall, but the image has no density unevenness. D: The toner layer on the developing roller is somewhat uneven overall, and minute density unevenness occurs at the edges of the image.

[0268] <Durability evaluation> After the evaluation of the solid-color tracking ability, 30,000 images with a printing ratio of 1.0% were printed on evaluation paper in a normal temperature and humidity environment (temperature 25°C / relative humidity 50%). After leaving the paper to stand for 24 hours in the same environment, the same evaluation as for the solid-color tracking ability was performed on all solid-color images.

[0269] The solid image conformability was evaluated according to the above-mentioned evaluation criteria, and the image density difference before and after the durability test was compared to evaluate the durability based on the following criteria.

[0270] (Durability evaluation criteria) A: The change in image density before and after durability test is less than 0.05. B: The change in image density before and after durability test is 0.05 or more and less than 0.10 C: The change in image density before and after durability test is 0.10 or more and less than 0.20 D: The change in image density before and after durability is 0.20 or more

[0271] The developing roller was also visually observed to check for the presence or absence of contamination with metal compound particles such as polyvalent acid metal salt particles.

[0272] (Contamination assessment criteria) A: No contamination occurs up to 30,000 sheets. B: Slight contamination occurred with 30,000 sheets. C: Contamination occurred after 30,000 sheets, but not enough to cause any practical problems. D: Ugly contamination occurs at 30,000 sheets.

[0273] <Evaluation of low-temperature fixability> In a normal temperature and humidity environment (temperature 25°C / relative humidity 50%), the fixing temperature was changed in 5°C increments from 140°C using an LBP7600C modified to adjust the fixing temperature at a process speed of 290 mm / sec. The toner to be evaluated had a toner loading of 0.40 mg / cm 2 Print a solid image on LETTER size Business 4200 paper (XEROX, 75g / m 2 The image was formed on the recording medium at 7.35 kPa (75 g / cm 2 ) and then heated and pressed without oil to form a fixed image. 2 The fixed image was rubbed 10 times with a load of 10 ...

[0274] (Evaluation Criteria for Low Temperature Fixability) A: Less than 150℃ B: 150℃ or higher and less than 160℃ C: 160℃ or higher but lower than 170℃ D: 170℃ or more

[0275] [Table 4]

Claims

1. A toner having toner particles containing a binder resin, polyvalent acid metal salt particles of a polyvalent acid and a compound containing at least one metal element selected from the metal elements included in Groups 3 to 13 are present on the surface of the toner particles, In a reflected electron image of the toner taken at a magnification of 50,000 times using a scanning electron microscope, the area of ​​the polyvalent acid metal salt particles relative to the total number of the polyvalent acid metal salt particles is 100 nm 2 The following number ratio (%) is A, the area of ​​the polyvalent acid metal salt particles is 500 nm 2 When the percentage (%) of the number of particles is B, the following formula (1) and formula (2) are satisfied, 83.0≦A (1) 1.7≦B≦17.0 (2) In the reflected electron image, the area of ​​100 nm 2 The area ratio of the polyvalent acid metal salt particles is 0.3% or more and 16.0% or less. A toner characterized by:

2. In a reflected electron image of the toner taken at a magnification of 50,000 times using a scanning electron microscope, the area of ​​the polyvalent acid metal salt particles relative to the total number of the polyvalent acid metal salt particles is 100 nm 2 500nm or more 2 When the percentage of the following number (%) is C, The toner according to claim 1 , which satisfies the following formula (3): 3.0<C≦15.3 (3)

3. The average area of ​​the polyvalent acid metal salt particles is 10 nm 2 5000nm or more 2 3. The toner according to claim 1, wherein:

4. 4. The toner according to claim 1, wherein the coefficient of variation of the area of ​​the polyvalent acid metal salt particles is 10.0 or less.

5. The toner according to any one of claims 1 to 4, wherein in a reflected electron image of the toner taken at a magnification of 50,000 times using a scanning electron microscope, a ratio of an area of ​​the polyvalent acid metal salt particles to a total area of ​​a toner particle surface in an observed field of view is 1.1% or more and 26.3% or less.

6. The toner according to any one of claims 1 to 5, wherein, in a mapping analysis using an energy dispersive X-ray spectrometer (EDS) on a cross section of the toner particle observed with a transmission electron microscope (TEM), when an average value of height in a normal direction of the polyvalent acid metal salt particle is taken as Ha (nm), the following formula (4) is satisfied: 2.5≦Ha≦50.0 (4)

7. The metal element contained in the polyvalent acid metal salt particles is designated as metal element M, The amount of metal element M contained in the toner determined by fluorescent X-ray analysis is defined as M1 (detection intensity kcps), 1.0 g of the toner was dispersed in a mixed aqueous solution consisting of 31.0 g of a 61.5% by mass sucrose aqueous solution and 6.0 g of a 10% by mass neutral detergent aqueous solution for cleaning precision measuring instruments, which is composed of a nonionic surfactant, an anionic surfactant and an organic builder, and the dispersion was subjected to a process (a) in which the dispersion was shaken for 20 minutes at 300 times per minute using a shaker. The toner thus obtained was designated as toner (a); The amount of metal element M contained in the toner (a) determined by fluorescent X-ray analysis is M2 (detection intensity kcps). When The toner according to any one of claims 1 to 6, wherein M1 and M2 satisfy the following formula (5): 0.85≦M2 / M1 (5)

8. 8. The toner according to claim 1, wherein the toner particles have an organosilicon compound on the surface thereof.

9. 9. The toner according to claim 1, wherein the metal element is at least one selected from the group consisting of titanium, zirconium, copper, and aluminum.

10. A method for producing the toner according to any one of claims 1 to 9, A method for producing a toner, comprising the steps of: generating polyvalent acid metal salt particles of a polyvalent acid and a compound containing at least one metal element selected from the metal elements in Groups 3 to 13 of the toner; by reacting the compound containing the metal element with a polyvalent acid in an aqueous medium containing toner base particles and an organosilicon compound.

Citation Information

Patent Citations

  • Electrostatic charge image developing toner

    JP1996184988A

  • Toner

    JP2019128516A

  • Toner

    JP2020071363A

  • toner

    JP2021021789A

  • Toner

    JP2021021790A